PENGUASAAN KOSAKATA BAHASA MANDARIN SISWA KELAS VII SMP ISLAM ATHIRAH 2 MAKASSAR - Suhartatik Kuntari; Misnawaty Usman; Himala Praptami (Phonologie : Journal of Language and Literature, 2020)
Abstract. This research aims to obtain data on the level of vocabulary mastery of Mnadarin 7th grade students of SMP Islam Athirah 2 Makassar. The variables in this research are the level of vocabulary mastery in Mandarin and the factors that influence the vocabulary mastery of Mandarin. The population in this research were all 7th grade students of SMP Islam Athirah 2 Makassar who took specialization subjects in Mandarin with the total of 10 students. The research data were obtained by giving tests of Mandarin vocabulary mastery test and Likert scale to determine the factors that influence Mandarin vocabulary mastery. The data analysis technique is using the percentage technique. The results showed that the level of vocabulary mastery of 7th grade of SMP Islam Athirah 2 Makassar was in the good category (84.3%) with the factors that most influenced students mastery of Mandarin vocabulary were external factors in the aspect of teacher quality with a percentage of 93% and factors that were less influential were internal factors in the intelligence aspect with a percentage of 60%.